Vindication of Public Spheres: Critique Spaces for Critical Times - Muñoz Terrón, José María (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
In opposition to Reinhart Koselleck, the article raises again the relationship between times of crisis and public spheres and also the related «dialectics» of «secrecy» and «publicity». From this premise I interpret the contemporary crisis of models of political communication and participation, partly because of the impact of ITCs, alluding to recent socio-political phenomena in Spain, such as the 15M movement or Podemos party. The critique generates or sharpens crisis, and crisis expresse themselves in critique. The ideals of public sphere are reformulated on their own way with every crisis, to confront each society with the level of crisis of the times. In contrast to Koselleck, I reaffirme the normative requirement of public spheres as critical spaces, social realms, somewhere between politics and life-world.